Hard Turning of Stainless Steel using Wiper Coated Carbide Tool - Noordin, M.Y. (Inderscience Enterprises Ltd., 2007)
In recent years, tool manufacturers provide wiper geometry on cutting tools for turning applications with the purpose of increasing productivity and improving surface finish. Despite the potential added values, the use and study on wiper inserts are still lacking in quantity. This current study focuses on the performance of wiper coated carbide insert in hard turning with respect to tool life and surface finish. AISI 420 stainless steel hardened to 47–48 HRC was hard turned at various speeds and feeds ranging in finish turning parameters. Results showed that the maximum tool life of 18 min was achieved and the tool life decreased at higher cutting speeds and feeds. Wear occurred at both the rake and flank faces with crater formation exposing the carbide substrate indicating more severe wear on the rake face. The wiper coated carbide tool resulted in very fine surface finish, much better than the theoretical values.